Diagnostic accuracy and validity of three manual examination tests to identify alar ligament lesions: results of a blinded case-control study. (15th March 2019) - Harry Von, Piekartz; Maloul, Rakan; Hoffmann, Marisa; Hall, Toby; Ruch, Med Martin; Ballenberger, Nicolaus
ABSTRACT: Introduction : Tests to evaluate the integrity of the alar ligaments are important clinical tools for manual therapists, but there is limited research regarding their validity. Method : A single blinded examiner assessed alar ligament integrity using the lateral shear test (LST), rotation stress test (RST) and side-bending stress test (SBST) on a sample of convenience comprising 7 subjects with MRI confirmed alar ligament lesions and 11 healthy people. Alar ligament lesions were identified using both supine and high-field strength upright MRI. Results : The RST had a sensitivity of 80% and a specificity of 69.2%. The SBST and the LST both showed a sensitivity of 80% and a specificity of 76.9%. In cases where all three tests were positive, the specificity increased to 84.6%. Discussion : Tests of manual examination of alar ligament integrity have some diagnostic utility; however, these findings require further corroboration in a larger sample.